Tradisi Angngaru di Masyarakat Desa Bontolangkasa Kecamatan Bontonompo Kabupaten Gowa: (Studi Nilai-Nilai Budaya Islam) - Anugrah Saputra. F,; Rahmawati, (Tumanurung: Jurnal Sejarah dan Budaya, 2024)
Islamic cultural values ​​in the "angngaru" tradition in the people of Bontolangkasa Village, Bontonompo District, Gowa Regency, this research aims to find out; 1. Angngaru tradition in the people of Bontolangkasa Village, Bontonompo District, Gowa Regency, 2. Shift in the values ​​of the angngaru tradition in the people of Bontolangkasa Village, Bontonompo District, Gowa Regency. 3. Community response and Islamic values ​​to the angngaru tradition in Bontolangkasa Village, Bontonompo District, Gowa Regency. The type of research carried out is field research which involves direct observation of conditions in the field and direct involvement with the research object. However, researchers still pay attention to literature that is relevant to the research object. This research uses historical, religious, anthropological and social approaches. Data collection methods include direct observation in the field, interviews, and documentation. The results of this research show that: 1. The angngaru tradition in Bontolangkasa Village still maintains human values ​​in an effort to preserve ancestral heritage. 2. Shifts in the Angngaru tradition as local wisdom tend to experience changes in values ​​in practice, indicating the existence of internal factors and a lack of responsibility in maintaining the continuity of the tradition as a symbol of identity that must be maintained, not abandoned. 3. Islamic cultural values ​​are visible in angngaru activities, including religious, moral, social and spiritual economic values ​​in society.